Geno3D: automatic comparative molecular modelling of protein - Combet, Christophe; Jambon, Martin; Deléage, Gilbert; Geourjon, Christophe (Bioinformatics, 2002)
Geno3D (http://geno3d-pbil.ibcp.fr) is an automatic web server for protein molecular modelling. Starting with a query protein sequence, the server performs the homology modelling in six successive steps: (i) identify homologous proteins with known 3D structures by using PSI-BLAST; (ii) provide the user all potential templates through a very convenient user interface for target selection; (iii) perform the alignment of both query and subject sequences; (iv) extract geometrical restraints (dihedral angles and distances) for corresponding atoms between the query and the template; (v) perform the 3D construction of the protein by using a distance geometry approach and (vi) finally send the results by e-mail to the user. Availability: Free to academic users http://geno3d-pbil.ibcp.fr Contact: c.geourjon@ibcp.fr * To whom correspondence should be addressed.